A new species of the deepwater clingfish genus Kopua (Gobiesociformes: Gobiesocidae) from the East China Sea—an example of antitropicality? - Moore, Glenn I.; Hutchins, J. Barry; Okamoto, Makoto (Zootaxa, 2012)
A new species of deepwater clingfish, Kopua japonica sp. nov., is described from the East China Sea. It is distinguished fromthe other members of the genus by anal and dorsal fin ray counts and a unique arrangement of sensory pores on the head. It isalso the first record of the genus from the Northern Hemisphere and this record may be an important deepwater addition to antitropicality in marine fishes.